Improving Mathematical Argumentation Ability and Sociomathematical Norms Using Missouri Mathematics Project on Trigonometric Ratios - Nurruzzahra, Rezka Andiva; Maarif, Samsul (IndoMath: Indonesia Mathematics Education, 2024)
In quality mathematics learning, there must be interaction between learners and educators. The interaction referred to in this study covers mathematical argumentation and sociomathematical norms. Mathematical argumentation ability: pay attention to signs, notations, and symbols from mathematics and how to negotiate to understand mathematical ideas. This study aims to analyze the improvement of mathematical argumentation ability and sociomathematical norms using the Missouri Mathematics Project on trigonometric ratios material. This research approach is quantitative. At the same time, the method used is a quasi-experiment with a non-equivalent control group design. The sample in this study was 51 learners. Data were analyzed by Two-Way ANOVA test with the conclusions: 1) The improvement of mathematical argumentation ability using the Missouri Mathematics Project learning model is better than the problem-based learning model; 2) There are differences in mathematical argumentation ability based on aspects of sociomathematical norms (high, medium and low); 3) There is no interaction between learning model and sociomathematical norms on mathematical argumentation ability.